Given `f(x)=-(x-1)(x+2)^3` :

(1) The y-intercept is found when x=0, thus y=-(-1)(2)^3=8 and the **y-intercept is 8**

The x-intercept(s) are where y=0: 0=(x-1)(x+2)^3

By the zero product property, either x-1=0 and/or (x+2)^3=0. Thus the **x-intercepts are x=1 and x=-2**.

(2) **The e` `nd behavior is**`f(x)=-x^4` `...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Given `f(x)=-(x-1)(x+2)^3` :

(1) The y-intercept is found when x=0, thus y=-(-1)(2)^3=8 and the **y-intercept is 8**

The x-intercept(s) are where y=0: 0=(x-1)(x+2)^3

By the zero product property, either x-1=0 and/or (x+2)^3=0. Thus the **x-intercepts are x=1 and x=-2**.

(2) **The e` `nd behavior is** `f(x)=-x^4`` ` (See graph below). Expanding the binomials and multiplying, we see that this is a polynomial with highest degree 4 and leading coefficient -1. (Expands as `-x^4-5x^3-6x^2+4x+8` )

(3) Since this is a fourth degree polynomial, **the maximum number of turning points is 4-1=3.**

(4) Graph:

Graphed with y=x^4 on larger scale: